Outcome comparison between radiation therapy and surgery as primary treatment for dogs with periarticular histiocytic sarcoma: An Italian Society of Veterinary Oncology study. (1st June 2020) - Marconato, Laura; Sabattini, Silvia; Buchholz, Julia; Polton, Gerry; Finotello, Riccardo; Martano, Marina; Willman, Michael; Massari, Federico; Agnoli, Chiara; Gedon, Julia; Cancedda, Simona; Campigli, Michela; et al.
Abstract: Localized histiocytic sarcoma may occur as a primary lesion in periarticular tissues of large appendicular joints. Treatment options for the primary lesion include radical surgical excision, radiation therapy (RT), or both, in combination with chemotherapy for potential systemic metastases. In an effort to better characterize the time to progression (TTP) following surgical vs non‐surgical approaches for periarticular histiocytic sarcoma (PAHS), a contemporary European population of affected dogs was retrospectively surveyed. Medical records were queried for newly‐diagnosed PAHS cases undergoing surgery (predominantly limb amputation) or RT followed by systemic chemotherapy. Of 49 dogs, 34 underwent RT and 15 underwent surgery. All dogs received adjuvant chemotherapy. There was no statistically significant difference in TTP or overall survival between groups. The median TTP was 336 days for the operated dogs and 217 days for the irradiated dogs ( P = .117). The median overall survival time was 398 days for the operated dogs and 240 days for the irradiated dogs ( P = .142). On multi‐variable analysis, the variables significantly associated with an increased risk of both tumour progression and tumour‐related death were regional lymph node and distant metastasis at admission. Survival and local control rates following RT may be comparable to radical resection. These data may better inform shared decision‐making processes between multi‐disciplinary care providers and owners.